In Vitro and In Vivo Malondialdehyde Inhibition Activities of Stichopus hermanii and Spirulina platensis - Mega Safithri; Kustiariyah Tarman; Iriani Setyaningsih; Yanti Fajarwati; Imanniar Yuta Ellana Dittama (Bogor Agricultural University, Indonesia, 2022)
Previous research showed that Stichopus hermannii and Spirulina platensis had an antioxidant activity. It is indicated by the reduced malondialdehyde (MDA) level in the liver of the diabetic rats. However, the STZ administration did not significantly increase MDA concentration of diabetic rats' blood serum for 14 days. This research aimed to determine in vitro and in vivo MDA inhibition of S. hermanii and S. platensis. The in vitro antioxidant activity test was conducted using the MDA-TBA method, and a positive control used α-tocopherol. For in vivo experiment, diabetic rats (DM) were induced by streptozotocin for 21 days. Twenty-five rats which were divided into five groups: normal rat group (NA), diabetic rat group (DA), diabetic rat group + glibenclamide (DG), diabetic rats + Stichopus hermanii (SH), and diabetic rats + Spirulina platensis (SP). The in vitro results showed that the antioxidant activity of 25 ppm Spirulina platensis had the same MDA inhibitory activity as 200 ppm α-tocopherol, but 200 ppm Stichopus hermanii had lower inhibition than 200 ppm α-tocopherol. The in vivo result showed that Stichopus hermanii treatment was more effective in suppressing blood serum MDA concentration, but Spirulina platensis was more effective in suppressing liver MDA concentration.